THE CORRELATION BETWEEN STUDENTS‟ READING ABILITY AND THEIR ABILITY IN WRITING NARRATIVE TEXT AT THE FIRST SEMESTER OF THE ELEVENTH CLASS AT MA HIDAAYATUL ISLAMIYAH BANDAR LAMPUNG IN 2014/2015 - Alfiawati, Riska (LPPM STKIP PGRI Bandar Lampung, 2015)
Reading comprehension is an activity with a purpose. Writing is the way to communicate a message to a reader for a purpose. Through writing, one can explain or describe things as result people miles from us can get information by reading the written message.The method of this research was descriptive quantitative method. The population of this research was the students at the first semester of the eleventh class at MA Hidaayatul Islaamiyah Bandar Lampung consisting of 63 students in 2 classes. The samples of this research were 40 students. In taking the sample, the writer used stratified proportional random sampling technique.The result of calculation by using Product Moment formula showed that rxy was 0.63. It was proved that the correlation between students‟ reading ability and their writing narrative ability was high. After that, the writer consulted the result of rxy above into significant level 5% with N=40 and got 0.312. By the other words, the writer concluded that there is a significant correlation between students‟ reading ability and their writing narrative ability at the first semester of the eleventh class at MA Hidayatul Islaamiyah Bandar Lampung in 2014/2015.